THE REAL ESSENCE OF TEACHING THE TRADITIONS OF UZBEK CLASSICAL MUSIC TO STUDENTS: Yulyahshiyev Sherali Narzullayevich - Teacher at the Faculty Art stadies of Gulistan State University, Yulyahshiyev Sherali Narzullayevich (Лучшие интеллектуальные исследования, 2024)
his article describes the theoretical and practical foundations of forming the skills of students to work on themselves, teaching the traditions of Uzbek classical music to students in individual lessons of maqam performance. In solo singing lessons, it was discussed the importance of the teacher's guidance in the process of working on their performance techniques, the need to teach singing literacy, hard work, listening and respect for our national musical heritage